METFORMIN OR INSULIN IN GESTATIONAL DIABETES-A CONUNDRUM - Ali, Saima; Perveen, Saima; Sadaf, Farhadia; Naveed, Parveen; Ikram, Tabasum; Halimi, Suraya (Journal of Postgraduate Medical Institute, 2022)
Objective: To determine the effectiveness of metformin vs insulin for glycemic control in gestational diabetes mellitus. Methodology: This study was done in the Department of Gynecology and Obstetrics, Saidu Teaching Hospital Swat from November 2019 to May 2020. Ethical approval was taken from the hospital ethical and research committee. A sample of 93 patients in each group was taken as per WHO sample size calculation software. All female patients with singleton pregnancies having gestational diabetes diagnosed for the first time in current pregnancy with an age limit from 16-40 Years were included in this study. The lottery method was used for dividing patients into two groups, group A (Metformin) and group B (Insulin). SPSS 23.0 was used for the data analysis using frequencies and percentages and the Chi-Square test was used to compare the efficacy of drugs between the two study groups. Efficacy was checked by measuring 1-hour postprandial sugar levels, i-e; more or less than 140mg/ dl. A p-value less than or equal to 0.05 was considered statistically significant. Results: Total number of patients was 186 (93 in each group). The mean age in group A was 28±3.76 years compared to 27±3.13 years in group B. Good glycemic control out of our total 186 patients (93 in each group) was achieved in 80%(n-74) in Group A compared to 90% (n-84) in Group B with a p-value was 0.0403. Conclusion: The study concludes that metformin is non-inferior to insulin in controlling glucose levels in gestational diabetes mellitus.